Smart fan (digital thermometer and fan control) [microfilm] - Ahmad Salahuddin Mamat (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Electrical Engineering (Electronic) - Universiti Teknologi Malaysia, 2002